Terminal Synergetic Control for Variable Speed Wind Turbine Using a Two Mass Model - Chavez-Orostica, H; Cruchaga-Ssa., M; Castillo-Del Barrio, E; Diaz-Diaz, M; Rajendran, S (Institute of Electrical and Electronics Engineers Inc., 2021)
This paper proposes three different synergetic control algorithms for two mass models of variable speed wind turbine with wind estimator. The wind turbine is modeled by a two-mass model that deals with wind turbine nonlinear aerodynamics and its flexible models. The controllers aim to maximize the captured energy from the wind whilst reducing the load level of the drive train. Initially, some of the conventional controllers such as sliding mode and integral sliding mode controllers are considered. Nonetheless, these controllers introduce more transient loads. To overcome these issues, a synergetic and terminal synergetic with integral based macro variable are proposed for a two-mass model wind turbine. These proposed controllers are verified through simulation and Fatigue, aerodynamics, structures, and turbulence 600kW model. The simulation results affirm that the terminal synergetic-based integral controller improves transient load reduction than other controllers. © 2021 IEEE.